Award "Dušan Bandić" for the year 2021 - Editorial Board (Etnoantropološki Problemi, 2022)
The "Dušan Bandić" award for the best book in the field of ethnology and anthropology in Serbia in 2021 was given to prof. Ildiko Erdei for the book Modern Life in Prime Time Television, Evoluta, Belgrade.